The Influence of Work Motivation on Productivity: The Mediating Role of Work Discipline among Oil Palm Farmers - Ayu Wulandari; Makmur Makmur; Hendry Kurniawan; Zuraida Hassan (PT. Hidayat Muda Intelektual, 2026)
This study examines the direct and indirect relationships between work motivation, work discipline, and work productivity among oil palm farmers in Tapung Jaya Village. In smallholder agricultural systems, productivity is not only influenced by technical capacity but also by psychological and behavioral factors. This research applies a quantitative explanatory design using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 89 oil palm farmers selected from a population of 735 farmers using the Slovin formula with a 10% margin of error. Measurement model evaluation confirmed satisfactory validity and reliability. The structural model indicates that work motivation has a significant positive effect on work productivity (β = 0.532; p = 0.001). However, work motivation does not significantly affect work discipline (β = 0.155; p = 0.516), and work discipline does not significantly affect work productivity (β = 0.256; p = 0.363). Furthermore, work discipline does not mediate the relationship between work motivation and productivity (indirect β = 0.040; p = 0.654). These findings suggest that motivation functions as the primary determinant of productivity in decentralized farming contexts, while discipline does not operate as an intervening mechanism. The study contributes to contextualized organizational behavior literature by demonstrating that mediation models commonly validated in formal employment settings may not automatically apply to smallholder agricultural systems. Practically, productivity enhancement strategies should prioritize strengthening farmers’ motivational drivers rather than focusing solely on compliance-based discipline interventions.